Penerapan Sistem SCADA Audit Energi Listrik Berbasis Raspberry-Pi Codesys Dengan Komunikasi Modbus TCP Di Workshop Elektro Politeknik Enjinering Indorama. - Yuda Muhammad Hamdani; Sarosa Castrena Abadi; Dani Usman (P3M Politeknik Negeri Indramayu, 2022)
The Covid-19 pandemic has an impact on almost all sectors of people's lives including the industrial sector.. According to Director of Energy Conservation Haryanto, the efforts that the industry can do to survive the current pandemic period is with conservation and energy efficiency, because when an industry has implemented an energy efficiency system, the industry will be able to reduce energy costs and reduce carbon dioxide (CO2) emissions. This research aims to create a prototype system that can support effective and efficient energy utilization efforts through the monitoring system of electricity use in the Politeknik Enjinering indorama Electrical department Workshop building so that it is expected to be used as a reference for energy audit systems both in the community environment and in the Politeknik Enjinering Indorama in order to aim for energy utilization. In this system Nodemcu ESP 8266 which acts as an RTU (Remote Transfer Unit) will send the results of processing data measurement sensor PZEM 004t to MTU (Master Transfer Unit) Raspberry pi using the Communication Protocol Modbus TCP, then the data received by MTU from RTU will be displayed to the display HMI (Human Machine Interface) Webvisu from Codesys so that sensor measurement data can be monitored in real time in the Politeknik Enjinering indorama Electrical department Workshop building either through the Computer or mobile phone. Based on the results of PZEM04T sensor testing for energy use for 30 days obtained the largest energy usage data, namely on line 1 of 83235.31 KWh, on line 2 of 79122.49 KWh and on line 3 of 26289.15 with accuracy rates for each line1, 2 and 3 which is 4.46%, 4.87% and 9.89%. The conclusion of this study that the system successfully functioned in accordance with the purpose of the study is to monitor the use of electrical energy in the Electrical Engineering wokshop building both through mobile phones and PCs in real time to be further referenced to the process of effective and efficient energy utilization in the future.Keywords: Energy Audit; PZEM04T; Raspberry Pi Codesys; Modbus TCP.